Internet of things based learning media with problem solving approach: Its effect on higher order thinking skills - Liana, Yeni Rima; Linuwih, Suharto; Sulhadi, Sulhadi (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
This research analyzed media feasibility and effectiveness based on IoT with a problem-solving approach that provides real experience to improve students' HOTS on thermodynamics law material. The Borg & Gall method's research development simplification had three stages: preliminary study, development, and field testing. The research subjects consisted of four lecturers as expert validators, two physics teachers, and three groups consisting of 108 in science XI grade students of Senior High School in Batang Regency, Central Java. Data collecting techniques were using questionnaires, observation, interviews, and written tests. The results of the validation of media experts and material experts were 3.84 and 3.75, respectively. The results of teacher responses and students' responses were 3.92 and 3.50 in the excellent category. The product's effective contribution to improving HOTS from the Multivariate Test analysis on GLM based on the partial eta squared value was 85.9%. The mean difference (MD) test results were -30.600 for the experimental group, while the control groups were -5.879 and -16.125, respectively. The more negative the Mean Difference (MD) score, the higher the students' HOTS. This shows that there is an experimental group giving improved scores better than the control group. This shows that there is an experimental group giving improved scores better than the control group. IoT is an opportunity for teachers to see technology as part of education because technology is the current millennial generation's cultural artifact.